Oil Shocks and External Balances. (IMF Working Papers; Working Paper ;, 2007)
This paper studies the effects of demand and supply shocks in the global crude oil market on several measures of countries' external balance, including the oil and non-oil trade balances, the current account, and changes in net foreign assets (NFA) during 1975-2004. We explicitly take a global perspective. In addition to the U.S., the Euro area and Japan, we consider a number of country groups including oil exporters and middle-income oil-importing economies. We find that the effect of oil shocks on the merchandise trade balance and the current account, which depending on the source of the shock can be large, depends critically on the response of the nonoil trade balance, and differs systematically between the U.S. and other oil importing countries. Using the Lane-Milesi-Ferretti NFA data set, we document the presence of large and systematic (if not always statistically significant) valuation effects in response to oil shocks, not only for the U.S., but also for other oil-importing economies and for oil exporters. Our estimates suggest that increased international financial integration will tend to cushion the effect of oil shocks on NFA positions for major oil exporters and the U.S., but may amplify it for other oil importers.